Between-Group Inequality May Decline despite a Rising Skill Premium - Imran Aziz; Guido Matias Cortes (Institute of Labor Economics (IZA), 2021)
A vast literature aimed at understanding the nature and causes of wage inequality focuses on the skill premium as a key object of interest. In an environment where both the skill premium and the share of skilled workers are changing, however, the between-skill-group component of inequality may fall even as the skill premium rises â exteuro“ a pattern that is indeed observed in the U.S. and in many local labor markets during the 2010s. Understanding the evolution of the skill premium is therefore not always useful in terms of understanding why broad inequality measures are changing.
Keywords: J31; J21; J24; 330; between-group inequality; skill-biased technical change; skill premium